2022
DOI: 10.1021/acs.jmedchem.1c01973
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Synthesis, and Structure–Activity Relationship Study on Daphnane and Tigliane Diterpenes as HIV Latency-Reversing Agents

Abstract: Three new diterpenes, stellejasmins A (1) and B (2) and 12-O-benzoylphorbol-13-heptanoate (3), were isolated from the roots of Stellera chamaejasme L. The structures of 1–3 were elucidated by extensive NMR and mass spectroscopic analyses. Compounds 1 and 2 are the first derivatives containing a hydroxy group at C-2 in the family of daphnane and tigliane diterpenes. The presence of a chlorine atom in 1 is unique in the plant metabolite. Compound 3 has an odd-number acyl group, which is biosynthetically notable.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…TLC and HPLC analyses showed that 7 was the only observable product of the reaction. It is noted that 7 can be partially converted to 3 when subjected to protic solvents. , Initially, we planned to utilize NMR experiments based on hydrogen and deuterium exchange to determine the cyclization of the ortho ester fragment in 7 . Regrettably, during the process of dissolving 7 in CD 3 OH for NMR analysis, indications of partial conversion to 3 were detected in the 1 H NMR spectrum (Figure S1.7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TLC and HPLC analyses showed that 7 was the only observable product of the reaction. It is noted that 7 can be partially converted to 3 when subjected to protic solvents. , Initially, we planned to utilize NMR experiments based on hydrogen and deuterium exchange to determine the cyclization of the ortho ester fragment in 7 . Regrettably, during the process of dissolving 7 in CD 3 OH for NMR analysis, indications of partial conversion to 3 were detected in the 1 H NMR spectrum (Figure S1.7).…”
Section: Resultsmentioning
confidence: 99%
“…26,27 Initially, we planned to utilize NMR experiments based on hydrogen and deuterium exchange to determine the cyclization of the ortho ester fragment in 7. 28 Regrettably, during the process of dissolving 7 in CD 3 OH for NMR analysis, indications of partial conversion to 3 were detected in the 1 H NMR spectrum (Figure S1.7). Thus, compounds 3 and 7 have the same configurations at C-4.…”
Section: Journal Of Natural Productsmentioning
confidence: 99%
“…The GBVI/WSA 82 dG scoring function is a forcefield-based scoring function that has been successfully used in many systems, whose results were consistent with the experimental data. [83][84][85] In addition, Wang et al identified that MOE Dock has good performance for the top scored poses. 86 Therefore, the scoring function is applied in molecular docking studies, and five favorable poses are obtained for the complex of LSD1 and compound 52 (see Fig.…”
Section: Equilibrium Structure Of Lsd1-phenylcyclopropylamine Derivat...mentioning
confidence: 99%
“…Latency‐reversing agents (LRAs) are considered to be potential tools for eliminating HIV reservoir cells in the “shock and kill” HIV treatment strategy [5] . Particular protein kinase C (PKC) activators, such as phorbol esters, [6] ingenols, [7] bryostatins, [8] DAG‐lactones, [9] and benzolactams, [10] have been reported to be LRAs [11] . Unfortunately, their structures are somewhat limited; hence, LRAs with novel skeletons need to be further developed and the unprecedented structure of ansellone A ( 1 ) offers a new opportunity in this regard.…”
Section: Introductionmentioning
confidence: 99%